Evaluating the role of the National Museum of Iran in the development of cultural tourism - Omid Salek Farokhi; Seyedeh Yasamin Hosseini (Studia Periegetica, 2021)
In addition to acquainting the public with the culture of a particular region, cultural tourism creates economic opportunities. Taking into account various tourist sites, museums are definitely among the most important ones. In Iran, the National Museum is one of the most important museums because of its rich collection of historical monuments related to the ancient Persia and Islamic periods. The authors of this article analyse the role of the National Museum of Iran in the development of the country’s cultural tourism. The analysis is based on information obtained from the database of the Iranian Cultural Heritage Organization and the National Museum of Iran. Confirmatory factor analysis and structural equation modelling were employed for data analysis. The results confirm the importance of the National Museum of Iran in the development of cultural tourism.